The Influence of Product Quality, Price, And Electronic Word of Mouth on the Purchase Decision of Kopi Tuku in Surabaya City, Merr Branch on Kopi Susu Tetangga Consumers - Silvia, Sukaina Abir; Kusuma, Yanda Bara (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of Product Quality, Price and Electronic Word of Mouth on Purchasing Decisions of Kopi Susu Tetangga Toko Kopi Tuku Merr branch, Surabaya. Coffee is not just a drink but has become a lifestyle of Indonesian people in their daily lives. The selection of coffee products is inseparable from the quality of the product, price and ewom of the product which influences people's purchasing decisions. The type of research used in this study is associative research with quantitative methods. The sampling technique used is probability sampling with the slovin sampling method. The data in this study are primary data and secondary data. Primary data was obtained from questionnaires filled out by respondents, while secondary data came from sources relevant to the topic. The results of this study indicate that product quality has a significant effect on purchasing decisions, price has a significant effect on purchasing decisions, and E-WOM has a significant effect on purchasing decisions. Not only that, simultaneously the three variables have a significant effect on purchasing decisions. Therefore, this study emphasizes the importance of the role of product quality, price, and E-WOM in product marketing strategies in order to strengthen consumer purchasing decisions.